Online Community of Open Code Development Project (International Journal of Engineering and Computer Science, 2018)
Today’s first technical need is a free platform for usability and if this platform could be customized by the user itself then it creates a unique community named as Open Source. This community provides many different technicalities in operating systems, applications, software, gaming etc. How this community takes its members and let them open their codes to the world for better use and modification. This is what we actually need to know about, how the biggest free and open source community gets its work, develops it, distributes it, use it and modify it without directly monitoring by the profit industries. Their work interacts with many e-commerce or e-businesses missions. Today every computer science student, lecturer, professor or administration should aware of this free and open source development phenomenon to participate with ongoing easy, batter, secure and modifiable